Resource flow or yardstick competition: spatial dependence of educational expenditure among prefecture-level cities. Issue 5 (4th October 2021) - Tian, Chuanhao; Teng, Yu; Guo, Hai (David)
Abstract: Primary and secondary education, provided by the local governments in China, plays an important role in attracting talented migrants. The race for talent and the education assessment from the top encourage local governments to compete with its neighboring localities in public education spending. Two theoretical frameworks can be applied to explain such strategic interactions among local governments—the resources-flow model and yardstick competition model. Using panel data of China's prefecture-level cities from 2007 to 2016, this article conducts a spatial econometric analysis to test the two aforementioned models empirically. The estimation results show that aside from a significant positive spatial dependence of education expenditures among local government in the same province, it also occurs among prefecture-level cities in different provinces. Indeed, based on the data that demonstrated the comparison among cities in different provinces with similar economic distance is stronger than that with closer geographical distances.